SIKAP RELATIF DAN KOMITMEN JANGKA PANJANG KONSUMEN DALAM MODEL LOYALITAS (Studi Kasus pada PT. Garuda Citilink) - Edwin Japarianto (Jurnal Manajemen Pemasaran, 2010)
The main objective of this research is to clarify a impact of relative attitude and long term commitment to consumer loyalty Garuda Citilink, Attitude observed by the dimention of: Personal Experience, Reference Group, Promotion. Commitment observed by the dimention of: Social Benefit, Comfortable benefit and Special Cases benefit and customer loyalty observed by the dimention of: satisfaction and willingness to buy. Using Path Analysis, the result of this research indicates that customer loyalty can be influence by customer commitment.